Heuristics and stock buying decision: Evidence from Malaysian and Pakistani stock markets - Khan, H.H.; Naz, I.; Qureshi, F.; Ghafoor, A. (Elsevier, 2017)
Applying both qualitative and quantitative approaches, we examine whether or not investors fall prey to three heuristics; namely, anchoring and adjustment, representativeness, and availability, while investing in stocks. We also compare investors’ vulnerability to these heuristics based on their economic association, their type and demographic factors such as income, education and experience. For the data collection, a self-constructed questionnaire was administered to investors in the Malaysian and Pakistani stock exchanges. Data has been analyzed through description, correlation and regression analysis. The results indicate that all three heuristics are likely to affect the investors’ stock buying decisions. The effect of heuristics is similar across the sample countries, the type of investors, and the income groups. However, the investors with a higher level of education and more experience are less likely to be affected by the heuristics.